Complex Bone Tumors of the Trunk—The Role of 3D Printing and Navigation in Tumor Orthopedics: A Case Series and Review of the Literature - Schulze, Martin; Gosheger, Georg; Bockholt, Sebastian; De Vaal, Marieke; Budny, Tymo; Tönnemann, Max; Pützler, Jan; Bövingloh, Albert Schulze; Rischen, Robert; Hofbauer, Vincent; Lübben, Timo; Deventer, Niklas; et al. (Journal of personalized medicine, 2021)
The combination of 3D printing and navigation promises improvements in surgical procedures and outcomes for complex bone tumor resection of the trunk, but its features have rarely been described in the literature. Five patients with trunk tumors were surgically treated in our institution using a combination of 3D printing and navigation. The main process includes segmentation, virtual modeling and build preparation, as well as quality assessment. Tumor resection was performed with navigated instruments. Preoperative planning supported clear margin multiplanar resections with intraoperatively adaptable real-time visualization of navigated instruments. The follow-up ranged from 2–15 months with a good functional result. The present results and the review of the current literature reflect the trend and the diverse applications of 3D printing in the medical field. 3D printing at hospital sites is often not standardized, but regulatory aspects may serve as disincentives. However, 3D printing has an increasing impact on precision medicine, and we are convinced that our process represents a valuable contribution in the context of patient-centered individual care.